2017
DOI: 10.18203/2394-6040.ijcmph20174221
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and pattern of self-medication among undergraduate students in a medical college of Kolkata

Abstract: Background: Self-medication is quite a prevalent public health problem in every part of the world. It can cause serious harms to the recipients through various implications like adverse drug reactions, incomplete cure, drug dependence etc. Medical students are in a unique position for wide practice of self-medication. The current study aimed to estimate the prevalence and to find out the existing knowledge, attitude and pattern of practice regarding self-medication among the undergraduate medical students of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 9 publications
8
18
0
Order By: Relevance
“…The findings were in congruence with other studies. 3,6,7,9 Majority (38%) of the respondents gathered information about self medication from the previously prescribed medicines of physicians followed by using medical textbooks (36%), self decision (33%), opinion from family/friends (26%), online through internet (22%) which was consistent with the other research work done by Jakaria. M et al and Seam MOR et al where students learned medications from doctor's prescription provided during their previous illness.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The findings were in congruence with other studies. 3,6,7,9 Majority (38%) of the respondents gathered information about self medication from the previously prescribed medicines of physicians followed by using medical textbooks (36%), self decision (33%), opinion from family/friends (26%), online through internet (22%) which was consistent with the other research work done by Jakaria. M et al and Seam MOR et al where students learned medications from doctor's prescription provided during their previous illness.…”
Section: Discussionsupporting
confidence: 82%
“…In studies conducted in developing countries, the prevalence of self medication was shown to be 94% in Oman, 90% in Iran, 65% in India, 62.9% in Egypt. 3,4,6,[9][10][11] Poor implementation of pharmaceutical rules due to various reasons like lack of adequate supervision by the concerned authorities may be the reason for high prevalence of self medication.…”
Section: Discussionmentioning
confidence: 99%
“…These finding were similar to earlier findings. 7,13 With best of author's knowledge, no Indian data is available for allied health and physiotherapy students. But few studies have been done on nursing students.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were noticed in previous studies. 7,11 Dental students have reported cough/ common cold as the most common symptom followed fever. This outcome was similarly noticed in former study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation